2001
DOI: 10.1046/j.1365-2958.2001.02649.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of tyrosine 972 of the Helicobacter pylori CagA protein is essential for induction of a scattering phenotype in gastric epithelial cells

Abstract: Helicobacter pylori colonizes the human stomach and is the causative agent of a variety of gastric diseases. After bacterial attachment, the H. pylori CagA protein is translocated into gastric epithelial cells and tyrosine phosphorylated. This process is associated with characteristic cytoskeletal rearrangements, resulting in a scatter factor‐like (‘hummingbird’) phenotype. In this study, using a cagA mutant complemented with wild‐type cagA and transiently expressing CagA in AGS cells, we have demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
164
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(176 citation statements)
references
References 57 publications
10
164
1
1
Order By: Relevance
“…1b). The 'hummingbird' effect has previously been shown to be dependent upon an intact cagPAI and phosphorylation of translocated CagA (Backert et al 2001;Segal et al 1999). Consistent with this, the P12ΔcagA mutant did not induce 'hummingbird' morphology in infected AGS cells (Fig.…”
Section: H Pylori-mediated Repression Of Host Hsps Expression Is Cagsupporting
confidence: 77%
See 1 more Smart Citation
“…1b). The 'hummingbird' effect has previously been shown to be dependent upon an intact cagPAI and phosphorylation of translocated CagA (Backert et al 2001;Segal et al 1999). Consistent with this, the P12ΔcagA mutant did not induce 'hummingbird' morphology in infected AGS cells (Fig.…”
Section: H Pylori-mediated Repression Of Host Hsps Expression Is Cagsupporting
confidence: 77%
“…Wild-type H. pylori strain P12 (P12wt) and its CagAdeficient isogenic mutant (P12ΔcagA) were used to infect the gastric adenocarcinoma cell line AGS to model H. pylori infection of gastric epithelia in vitro (Backert et al 2001;Kwok et al 2002;Kwok et al 2007). Following 24 h of infection, HSP expression was quantitated by Western blot analysis.…”
Section: H Pylori-mediated Repression Of Host Hsps Expression Is Cagmentioning
confidence: 99%
“…CagA is one of the cag PAI encoded genes. Upon attaching to the mucosal epithelial cells, cag PAI secretion system transports CagA into the host cells, causing actin cytoskeleton rearrangement into "Hummingbird" phenotype (Backert et al, 2001). These studies link SRF to the main cause of peptic ulcer.…”
Section: Srf In Ulcer Healingmentioning
confidence: 98%
“…Previous studies have shown that the CagA cytotoxin is directly injected into epithelial cells via a type IV secretion system, encoded by genes located in the cag -pathogenicity island (cag-PAI) [1,4,5]. In the host cell, CagA localises to the inner surface of the plasma membrane and undergoes phosphorylation on specific tyrosine residues within repeating penta amino acid Glu-Pro-Ile-Tyr-Ala (EPIYA) motifs, and in some cases Glu-Pro-Ile-Tyr-Thr (EPIYT), present at the C-terminus of the protein [2,6,7]. Tyrosine phosphorylation is carried out by host cell kinases such as Abl and Src [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In the host cell, CagA localises to the inner surface of the plasma membrane and undergoes phosphorylation on specific tyrosine residues within repeating penta amino acid Glu-Pro-Ile-Tyr-Ala (EPIYA) motifs, and in some cases Glu-Pro-Ile-Tyr-Thr (EPIYT), present at the C-terminus of the protein [2,6,7]. Tyrosine phosphorylation is carried out by host cell kinases such as Abl and Src [6,8,9]. The tyrosine phosphorylated CagA binds to a cytoplasmatic Src Homology 2 (SH2) domain of Src Homology 2 phosphatase 2 (SHP-2).…”
Section: Introductionmentioning
confidence: 99%